The Effects of Brainstorming Methods on The Ability to Express Opinions on History Studies at Almaarif Singosari Islamic High School - Fika Fatchul Nur Wakhidah; Aditya Nugroho Widiadi; Wahyu Djoko Sulistyo (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
This study aims to determine the effect of using the brainstorming learning method on the ability to express opinions of class XI students at Almaarif Singosari Highschool in learning history. The research design used a quantitative method with a pre-experimental type of one group pretest-posttest design. The research instrument used was a description test as the main instrument, used to see the ability to express students' opinions in writing and observation as a companion instrument to see the ability to express students' opinions orally. The analysis of the data used is the paired sample t-test and normality test. The results of the study in test scores showed an increase from the pretest average of 55.97 to 68.96 on the posttest average. Then on the observation sheet, students also have an increase in the ability to express opinions orally. The increase was seen from the average before the implementation, which was 31,76 to 66,17 when the brainstorming method was implemented in the class. Furthermore, from hypothesis testing, the results obtained are sig.0,000 sig 0.05. So, from this, it can be concluded that the brainstorming method affects the ability to express students in the experimental class.